Fuel Emission Projection of Indonesian Manufacturing Industry Towards Net Zero Emissions 2060 - Annisa Ayu Fawzia; Emilya Nurjani; Rika Harini (Magister Program of Material Science, Graduate School of Universitas Sriwijaya, 2026)
The growth of Indonesia’s manufacturing industry has the potential to increase greenhouse gas (GHG) emissions. Therefore, this sector needs to become a key focus of emission control programs, aligned with the United Nations Sustainable Development Goals. The limited research comparing the contributions of manufacturing subsectors to national GHG emissions motivated this study. This research aims to (i) estimate projected GHG emissions from fuel consumption across medium- and large-scale manufacturing subsectors in Indonesia from 2025 to 2060 and (ii) determine the energy matrix with the lowest-emission scenario approaching the NZE-2060. GHG emissions are projected using LEAP software under four scenarios: business as usual (BAU), emission reduction (ER), clean transition 1 (CT-1), and clean transition 2 (CT-2). The projection results show that GHG emissions in 2060 will reach 593,520.08 Gg CO2eq (BAU), 320,734.36 Gg CO2eq (ER), 125,835.03 Gg CO2eq (CT-1), and 72,834.14 Gg CO2eq (CT-2). The CT-2 scenario produces the lowest emissions closest to the NZE-2060 target, while the ER scenario represents the most realistic pathway considering Indonesia’s renewable energy potential, but has to be complemented by other decarbonization efforts such as CCU/CCS technologies and biomass certification to achieve NZE-2060.